Remote Epitaxy of Cubic Gallium Nitride on Graphene‐Covered 3C‐SiC Substrates by Plasma‐Assisted Molecular Beam Epitaxy - Littmann, Mario; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Selective Area Growth of Cubic Gallium Nitride in Nanoscopic Silicon Dioxide Masks - Meier, Falco; Littmann, Mario; Bürger, Julius; Riedl, Thomas; Kool, Daniel; Lindner, Jörg; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Clean and Hydrogen‐Adsorbed AlInP(001) Surfaces: Structures and Electronic Properties - Glahn, Luis Joel; Ruiz Alvarado, Isaac Azahel; Neufeld, Sergej; Zare Pour, Mohammad Amin; Paszuk, Agnieszka; Ostheimer, David; Shekarabi, Sahar; Romanyuk, Oleksandr; Moritz, Dominik Christian; Hofmann, Jan Philipp; Jaegermann, Wolfram; Hannappel, Thomas; et al. (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Funktionsoptimierte AM-Gestaltung eines E-Rotors - Magerkohl, Sebastian; Zimmer, Detmar; Tasche, Lennart; Schaper, Mirko; Urbanek, Stefan; Ponick, Bernd (antriebstechnik - Zeitschrift für Konstruktion, Entwicklung und Anwendung von Antrieben und Steuerungen)
Die Additive Fertigung bietet ein hohes Maß an Gestaltungsfreiheit und ermöglicht die wirt-schaftliche Nutzung von konventionell schwer zu verarbeitenden Materialien. Diese Merk-male ermöglichen neuartige Lösungsansätze bei Funktionsbauteilen in fast allen Anwen-dungsbereichen. Dieses Potential kann auch im Elektromaschinenbau genutzt werden. Am Bespiel des Rotors einer permanentmagneterregten Synchronmaschine (PMSM) lassen sich die Herausforderungen und Möglichkeiten exemplarisch beschreiben.

GaInP/AlInP(001) Interfaces from Density Functional Theory - Meier, Lukas; Schmidt, Wolf Gero (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Photoluminescence Line‐Shape Analysis of Highly n‐Type Doped Zincblende GaN - Baron, Elias; Goldhahn, Rüdiger; Deppe, Michael; As, Donat Josef; Feneberg, Martin (physica status solidi (b))

Molecular Beam Epitaxy Growth and Characterization of Germanium‐Doped Cubic Al x Ga 1− x N - Deppe, Michael; Henksmeier, Tobias; Gerlach, Jürgen W.; Reuter, Dirk; As, Donat Josef (physica status solidi (b))

Band Alignment at Ga x In 1– x P/Al y In 1– y P Alloy Interfaces from Hybrid Density Functional Theory Calculations - Meier, Lukas; Braun, Christian; Hannappel, Thomas; Schmidt, Wolf Gero (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Molecular Beam Epitaxy Growth and Characterization of Germanium‐Doped Cubic Al x Ga 1− x N - Deppe, Michael; Henksmeier, Tobias; Gerlach, Jürgen W.; Reuter, Dirk; As, Donat J. (physica status solidi (b))

Electric Field Induced Raman Scattering at the Sb–InP(110) Interface: The Surface Dipole Contribution - Esser, Norbert; Schmidt, Wolf Gero (physica status solidi (b))